Spectrophotometric Determination of Trace Amounts of Beryllium in Natural Water Using Mean Centering of Ratio Spectra Method and Partial Least Squares Regression - CHAMSAZ, MAHMOUD; HOSSEIN ARBABZAVAR, MOHAMMAD; HEIDARI, TAHEREH; HAJINIA, AKRAM; SALEHI, THIERY (Asian Journal of Chemistry, 2010)
Two simple chemometrics methods for spectrophotometric determination of trace amounts of beryllium by mean centering of ratio spectra (MCRS) and partial least squares (PLS) regression are described. Thorin at pH = 10.5 was used as a chelating agent. The proposed methods evaluate and eliminate the blank bias error present in such procedure. Under the optimized conditions, analytical characteristics of the mean centering of ratio spectra method were obtained. The calibration curve was linear over the range of 10-600 ng mL-1 of Be2+. The concentration detection limit of 2.56 ng mL-1 was achieved. The relative standard deviation for six replicate measurements of 200 ng mL-1 beryllium was 4.0 %. Relative error of prediction for applying the partial least squares method to 5 synthetic samples in the range of 10-600 ng mL-1 was 3.2 %. Analysis of spiked tap water, using both proposed methods, gave results which are in good agreement with their beryllium contents.